At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To find the position function [tex]\( s(t) \)[/tex] from the given velocity function [tex]\( v(t) \)[/tex] and initial position [tex]\( s(0) = 0 \)[/tex], we need to follow these steps:
1. Integrate the velocity function: The position function [tex]\( s(t) \)[/tex] is the integral of the velocity function [tex]\( v(t) \)[/tex]. Given:
[tex]\[ v(t) = 6t^2 + 6t - 9 \][/tex]
we will integrate [tex]\( v(t) \)[/tex] with respect to time [tex]\( t \)[/tex].
2. Compute the indefinite integral: Perform the integration of [tex]\( v(t) \)[/tex] term by term.
[tex]\[ \int (6t^2 + 6t - 9) \, dt \][/tex]
- Integrate [tex]\( 6t^2 \)[/tex]: [tex]\(\int 6t^2 \, dt = 2t^3 \)[/tex]
- Integrate [tex]\( 6t \)[/tex]: [tex]\(\int 6t \, dt = 3t^2 \)[/tex]
- Integrate [tex]\(-9 \)[/tex]: [tex]\(\int -9 \, dt = -9t \)[/tex]
Combining these results, we get:
[tex]\[ \int (6t^2 + 6t - 9) \, dt = 2t^3 + 3t^2 - 9t + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
3. Apply the initial condition: Use the initial position [tex]\( s(0) = 0 \)[/tex] to determine the constant [tex]\( C \)[/tex].
[tex]\[ s(0) = 2(0)^3 + 3(0)^2 - 9(0) + C = 0 \][/tex]
This simplifies to [tex]\( C = 0 \)[/tex].
4. Write the final position function: Substitute [tex]\( C = 0 \)[/tex] back into the expression for [tex]\( s(t) \)[/tex].
[tex]\[ s(t) = 2t^3 + 3t^2 - 9t \][/tex]
Therefore, the position function [tex]\( s(t) \)[/tex] is:
[tex]\[ s(t) = 2t^3 + 3t^2 - 9t \][/tex]
1. Integrate the velocity function: The position function [tex]\( s(t) \)[/tex] is the integral of the velocity function [tex]\( v(t) \)[/tex]. Given:
[tex]\[ v(t) = 6t^2 + 6t - 9 \][/tex]
we will integrate [tex]\( v(t) \)[/tex] with respect to time [tex]\( t \)[/tex].
2. Compute the indefinite integral: Perform the integration of [tex]\( v(t) \)[/tex] term by term.
[tex]\[ \int (6t^2 + 6t - 9) \, dt \][/tex]
- Integrate [tex]\( 6t^2 \)[/tex]: [tex]\(\int 6t^2 \, dt = 2t^3 \)[/tex]
- Integrate [tex]\( 6t \)[/tex]: [tex]\(\int 6t \, dt = 3t^2 \)[/tex]
- Integrate [tex]\(-9 \)[/tex]: [tex]\(\int -9 \, dt = -9t \)[/tex]
Combining these results, we get:
[tex]\[ \int (6t^2 + 6t - 9) \, dt = 2t^3 + 3t^2 - 9t + C \][/tex]
where [tex]\( C \)[/tex] is the constant of integration.
3. Apply the initial condition: Use the initial position [tex]\( s(0) = 0 \)[/tex] to determine the constant [tex]\( C \)[/tex].
[tex]\[ s(0) = 2(0)^3 + 3(0)^2 - 9(0) + C = 0 \][/tex]
This simplifies to [tex]\( C = 0 \)[/tex].
4. Write the final position function: Substitute [tex]\( C = 0 \)[/tex] back into the expression for [tex]\( s(t) \)[/tex].
[tex]\[ s(t) = 2t^3 + 3t^2 - 9t \][/tex]
Therefore, the position function [tex]\( s(t) \)[/tex] is:
[tex]\[ s(t) = 2t^3 + 3t^2 - 9t \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.